Acute Disseminated Encephalomyelitis Secondary to Herpes Virus Infection in a Child - Ouassou, Zakaria; Motiaa, Youssef; Bentalha, Aziza; El Koraichi, Alea; El Kettani, Selma Ech-Chrif (Journal of Nepal Paediatric Society, 2018)
The acute disseminated encephalomyelitis ADEM is a rare form of encephalitis. We report a case after herpes infection. The diagnosis was based on the existence of post-infectious and neurological signs and demyelinating reaching the white matter in the magnetic resonance imaging MRI. The outcome was favourable after treatment with high-dose steroids.